Understanding adult learners' preferences for classroom social environment - Thomas Valentine; Kwang Kim (Adult Education Research Conference, 1994)
This exploratory study sought to identify learner characteristics that explain preferences for classroom social environment. Data about preferences for classroom social environment and about learner characteristics were collected by means of a self-completion, selected-response survey instrument administered in a variety of adult education settings. Data were then subjected to both simple and multiple regression analyses. Educational attainment, social introversion/extroversion, and gender were found to be the best predictors of environmental preferences.